Dinamika Modernisasi Hukum Islam: Tinjauan Historis dalam Pembacaan Mazhab Sociological Jurisprudence - Zayyadi, Ahmad (Fakultas Syariah IAIN Purwokerto, 2020)
This article explores the dynamics of the modernization of Islamic law using the sociological approach. The legal theory used is the history of modern law as a comparative Islamic law in the Muslim world related to its influence in Indonesia. The author associates the sociological jurisprudence with the dynamics of modernization of Islamic law in the Muslim world including Indonesia. The sociological jurisprudence is applied in the study of marriage law issues that still need efforts to modernize the law, because these problems continue to develop and the legal position must always be dynamic in responding to sociological problems that always live in society. Various theoretical influences in the sociology of law and also the sociological jurisprudence have a wider impact on the sociology of Islamic law. This effort to modernize Islamic law is part of the development of modernization theory in the sociology of law, which synergizes integratively between law and society and society and law proportionally. This article seeks to apply the sociology of law in general and the sociological jurisprudence in particular about family law with the case of sociological problems of Islamic law in Muslim societies such as Turkey, Egypt, and Indonesia.